1984
DOI: 10.1136/jnnp.47.4.333
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture versus medical treatment for migraine and muscle tension headaches.

Abstract: The thousands of patients attending general practitioners, hospitals, migraine clinics and non-medical practitioners and the profusion of drug regimes and physical methods offereu, all bear witness to the fact that the treatment of migraine and other sorts of headache is unsatisfactory. That this is so is realised by the public, who have become more interested in treatments that are offered outside the medical profession. Acupuncture in this country is provided by a great many non-medically qualified persons a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
7

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(36 citation statements)
references
References 3 publications
2
27
0
7
Order By: Relevance
“…3 They concluded that the evidence supports the role of acupuncture for the treatment of idiopathic headaches but is not conclusive. While some researchers recommended that acupuncture is valuable for various types of headache, including tension type and migraine, [4][5][6][7][8][9][10] others failed to demonstrate clinically significant differences. [11][12][13][14][15][16][17] Factors which make the practice of acupuncture unlikely to be acceptable to certain medical communities include the possibility of transmitting infection, the risk of visceral trauma, particularly pneumothorax, and the invasive nature of the practice in general.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 They concluded that the evidence supports the role of acupuncture for the treatment of idiopathic headaches but is not conclusive. While some researchers recommended that acupuncture is valuable for various types of headache, including tension type and migraine, [4][5][6][7][8][9][10] others failed to demonstrate clinically significant differences. [11][12][13][14][15][16][17] Factors which make the practice of acupuncture unlikely to be acceptable to certain medical communities include the possibility of transmitting infection, the risk of visceral trauma, particularly pneumothorax, and the invasive nature of the practice in general.…”
Section: Introductionmentioning
confidence: 99%
“…2 The effects of acupuncture on various types of headache have been studied widely. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] In a Cochrane review, Melchart et al compared the effectiveness of acupuncture with 'sham' (placebo) acupuncture and other interventions used to treat idiopathic (primary) headaches including tensiontype headache. 3 They concluded that the evidence supports the role of acupuncture for the treatment of idiopathic headaches but is not conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of acupuncture with transculaneous nerve stimulalion (TENS) carried out by Laitinen (53), and by Fox and Melzack (54) showed no significant differences in pain relief for low back pain. Loh et al (55), showed acupuncture to be lletter than o(hodox treatment in migraine and tension headaches whilst CLrnn et al (56) have demonstrated acupuncture to be superior to standard therapy In low back pain-This is not substantiated by Ahonen et al (57).…”
Section: Metlnds Of Acupuncturementioning
confidence: 65%
“…Die analgetische Wirkung der Akupunktur kann sich auch bei Kopfschmerzen organischer Ursache auswirken [20] und dann dazu führen, daß kostbare Zeit verlorengeht und wichtige diagnostische Schritte unterlassen werden.…”
Section: Praktisches Vorgehenunclassified